Digital Communication Ethics in Law Enforcement in the Community Environment - Anggraini, Dini; Fitri, Dwi; Munira, Nurul; Aprilia, Fani; Ariani, Melisa; Nazwa, Siti; Aldama, Bella; Julinda; Saputra, Zaki Ryan (MANDAILING GLOBAL EDUKASIA, 2025)
The rapid development of digitalization has brought significant changes to all aspects of life, especially the way humans communicate and law enforcement. As a widespread and interactive digital platform, social media provides a space for people to express themselves publicly. However, this freedom also brings new challenges, such as the spread of misinformation, hate speech, and defamation, which often result in legal action. In Indonesia, regulations regarding digital communication practices are mainly regulated through the Electronic Information and Transactions Law (UU ITE). Although the law is an important tool for maintaining social order, its implementation often triggers debate about the balance between protecting freedom of expression and the state's obligation to maintain social order. This article discusses the ethics of digital communication in the context of law enforcement, emphasizing the balance between protecting individual privacy and the public interest. The author discusses the various challenges faced in the implementation of the Electronic Information and Transactions Law (UU ITE) and considers its impact on human rights, especially in terms of freedom of expression and personal data protection. On the one hand, individuals have the right to maintain their privacy; on the other hand, the state has an obligation to maintain public security and control the spread of information that can disrupt public order. In this way, this article is expected to enrich the understanding of the dynamics of digital communication ethics in the legal field and provide input for better policy making in the future.